Semantic Multimedia 5th International Conference on Semantic and Digital Media Technologies, SAMT 2010. Saarbrücken, Germany, December 1-3, 2010. Revised Selected Papers - Declerck, Thierry; Granitzer, Michael; Grzegorzek, Marcin; Romanelli, Massimo; Rüger, Stefan; Sintek, Michael; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the revised selected papers of the 5th International Conference on Semantics and Digital Media Technologies, SAMT 2010, held in Saarbrücken, Germany, in December 2010. As a result of a highly selective review procedure, 12 full papers and 4 short papers were accepted for publication. The contributions present novel approaches for managing, distributing and accessing large amounts of multimedia material. The topics covered include semantic search, analysis and retrieval of images, audio, video, 3D/4D material as well as of computer generated multimedia content. Also addressed are issues relating to semantic metadata management, semantic user interfaces, and semantics in visualization and computer graphics.
Electronic reproduction.
Keywords: Multimedia systems -- Congresses; Semantic computing -- Congresses; Electronic book